COST ESTIMATE FOR FILLING WITH DIFFERENT MOTOR FUELS IN FREIGHTING BY LIGHT-DUTY VEHICLES - Banket, Mikhail; Shapoval, Dmitry; Eychler, Ivan; Pogulyaeva, Irina; Aleshkov, Denis (Journal of Applied Engineering Science, 2022)
The use of natural gas as a motor fuel in road transport can significantly reduce fuel costs and the adverse environmental impact of motor vehicles. However, an insufficiently developed infrastructure for compressed natural gas (CNG) constrains the growth in the number of natural gas-powered road transport enterprises. The limited number of automobile gas-filling compressor stations (AGFCS) increases the mileage of motor vehicles, which reduces the efficiency of natural gas use in road transport. This study aims to assess the costs of filling with different types of motor fuel regarding the overall costs of road freight. The scientific novelty of the work lies in establishing the dependence of costs for filling with motor fuel on the operational performance of vehicles and the development of fueling infrastructure of specific motor fuel types. For the first time, the authors evaluated the share of fueling costs for light-duty vehicles (LDVs) for different hydrocarbon fuels regarding the costs associated with the transportation process. It was found that the share of fueling costs varies depending on the type of hydrocarbon fuel used and can range from 1.5 to 15%, depending on the fueling infrastructure development. The results obtained can be used in decision-making on choosing the fuel type in the transportation process by LDVs to minimize overall costs.
Keywords: motor fuel, filling station, fueling costs, light-duty vehicles